Cooperative downloading with privacy preservation and access control for value-added services in VANETs. (2016) - Zhang, Wujun; Jiang, Shunrong; Zhu, Xiaoyan; Wang, Yumin
Value-added services in Vehicular Ad Hoc Networks (VANETs) have gained increasing popularity in recent years. However, Road Side Units (RSUs) cannot usually cover the whole region, resulting in intermittent connectivity. Therefore, how to download data continuously while preserving users' privacy remains an open problem. In this paper, we propose an efficient data downloading scheme based on users' cooperation, providing continuous downloading services even when the region is not completely covered by RSUs. Moreover, in order to protect data receivers' privacy and realise fine-grained access control, we employ Ciphertext Policy Attribute Based Encryption with Constant Length (CP-ABE-CL) with consideration of users' charge levels. The security analysis shows that our scheme can achieve mutual authentication for vehicles and RSUs, and realise fine-grained access control while preserving privacy of data receivers' identities. The performance analysis demonstrates that our scheme is efficient enough to be implemented in VANETs.